TYPES AND STAGES OF THE FIGHT AGAINST CORRUPTION - Bekdavlat Aliev (Scholar Express Journal, 2023)
The article analyzes the types and stages of the fight against corruption, which is considered the key to development. Also, the author expressed his opinion on the wide-scale reforms in the fight against corruption in the Republic of Uzbekistan in recent years based on various legal documents.
Keywords: Corruption; bribery; Liberal democracy